Karakteristik Kimiawi Enkapsulasi Minyak Ikan Berbahan Baku Patin dan Hiu dengan Penambahan Minyak Sawit Merah: Chemical Characteristics of Encapsulated Fish Oil from Pangasius and Shark with The Addition of Red Palm Oil - Dewita; Syahrul; Hidayat, Taufik; Fauzi, Muhammad (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Catfish and shark oil are fishery products that contain lots of fatty acids for health. The addition of red palm oil also has the potential to increase the fatty acid content of the product. This study aims to determine the best concentration of red palm oil in the fish oil encapsulation formulation. This research method includes fish oil encapsulation formulation with the addition of red palm oil treatment, testing the characteristics of fish oil including the peroxide number, free fatty acids, daniodic acid numbers, and fatty acids using Gas Chromatography (GC). The results showed that the F2 formula with the addition of 30% palm oil was the best formula favored by consumers in terms of color, taste, and smell. Formula F2 also has fatty acid values of SFA, MUFA and PUFA, namely palmitic acid 22.03%, oleic acid 32.71% and linoleic acid 31.84%. Formula F2 can be developed into functional products for health supplements